Towards the Poetics of Lyrical Realism in the Histories of Serbian Literature - Bojanić Ćirković, Mirjana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The subject of the paper is the analysis of the poetic qualities of the works of lyrical realists, but also pointing out the possibilities of deconstructing the aforementioned literary corpus, which mainly refers to three writers: Ivo Ćipiko, Petar Kočić, and Borisav Stanković. First, the periodizational limits of lyrical realism were explored and its ambivalent intra-periodizational and universal literary method character was pointed out. Through the works of lyrical realists, we saw the diachrony of their reception in literary history textbooks, but also in contemporary essays and monographs, which, along with a close reading of the works themselves, enabled us to summarize the implicitly poetic and explicit determinants of lyrical realism from the point of view of the creative process, the form of the work, the narrative world, and narrative strategies, without neglecting the specific poetic determinants of individual writers. From this point of view, the paper points to the possibilities of interpreting the lyrical layer of the realistic opus of Old and Southern Serbia. Following the mentioned parameters, we emphasized that the work of the writers of Old Serbia—Anđelko Krstić and Grigorije Božović—grows out of a deep attachment to the nature of the homeland and that on the level of internal form, it contains more poetic determinants of lyrical realists, as well as features of the modernization of prose, such as the psychological aspect of painting the struggle, internal focalized descriptions of the naturalistic style, the lyricalization of the narrative to the genre of the poem in prose, etc.